Pembuatan Augmented Reality dengan Unity 5.4 - Findi Irmaningsih; Sudarno (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2017)
Utilizing Technology that is no stranger to that phones so namely more efficient process to review access to the latest news, including a review of data from computer displays well as to review developments following the animation using 3Dimensi with era. Previous animation development Currently with singer Namely augmented reality images 2Dimensi if Seen From the smartphone camera Shown 3Dimensi object. The results obtained Singers Project is on an augmented reality applications with The panels can be used as Zoom Out, Zoom In, Rotate Right, Rotate Left, Up, Down, Left, Right, Next Scene and Previous Scene. In this study indicate that the use of 3D animation look more interesting because the object is highly visible and can be seen from different angles. Resolution and contrast image of the marker will very berpengaruhi of the result of making use of augmented reality